Supply Chain Sustainability Measurement in Telecommunications Industry in Indonesia - Nabil, Abdullah; Asrol, Muhammad (Engineering, MAthematics and Computer Science Journal (EMACS), 2024)
In the fiercely competitive telecommunications industry of Indonesia, the significance of innovation and perpetual improvement cannot be underestimated. It is imperative for businesses to explore the potential of sustainable supply chain management, as it allows for the integration of environmental, economic, and social dimensions. By implementing a comprehensive and thorough approach, this study offers a theoretical framework for measuring sustainable supply chain performance. Through qualitative and quantitative methods, you'll be able to identify the attributes that greatly impact the success of your sustainable supply chain management. On this research Analytic Hierarchy Process (AHP) utilize to define Consistency Ratio (CR) and weight between dimension using SuperDecisions software. Then, Multidimensional Scaling (MDS) is utilized to measure performance of supply chain sustainability. At the same time, a stress value also measured to indicate the sustainability measurement of one specific dimension is sufficient in accordance with existing condition or not. Next, to better indicate which attributes are most influential on improving dimensional sustainability performance, it is essential to conduct a sensitivity analysis and Montecarlo analysis for each attribute. In the end, this research successfully determined which attributes that influence sustainable supply chain management and measure the value of supply chain sustainability in the telecommunications industry in Indonesia.